When jokes are not funny - Humour and abuse in elite sport - Colm Hickey (Bern Open Publishing, 2023)
Joking and humour are central to the daily lives and lived experiences of professional elite athletes (Hickey, 2016; Roderick, 2006). Traditionally within sport, such discourses have been accepted as back and forth joking between teammates, athletes, and coaches, and should not be taken seriously by either the recipient or antagonist (Magrath, 2016). Although joking relations are widely assumed to be harmless (Plester, 2016), their characteristics and constant presence in the lives of professional and elite athletes share unmistakable similarities to forms of abuse (Jacobs et al., 2017; Mountjoy et al., 2016). Professional sport is an environment in which abuse is often present and condoned. More recently, the different forms of abuse that athletes are, and have been, exposed to have become more widely known (McMahon & McGannon, 2019). Examining professional football specifically, abusive practices are traditionally accepted and positioned as part of the cultural norms within footballing work environments (Kelly & Waddington, 2006). As part of their lived experiences in these environments, professional players both participate in and are the recipients of such abuse. Data were collected from 10 male participants (aged 18-30) by means of qualitative semi-structured vignette interviews. Each participant was interviewed on three separate occasions (30 interviews). The data and subsequent analysis illustrate how banter is an accepted and legitimised discourse within professional football, but promotes considerable anxiety, stress and unhappiness in work environments. Utilising a theoretical framework that combines elements of Goffman's (1959) Dramaturgy with notions of Possible Selves (Markus & Nurius, 1986), this investigation illustrates the impact of such abuse on English Premier League players. It illustrates how joking and humour, is better understood as a form of psychological emotional abuse, that it is normalised as workplace putdown humour and carries with it many elements that players find marginalising, deliberate and threatening to their identities and sense of professional security. This research offers a new critical perspective that provides a better understanding of the distinctive and intricate social discourses in the daily lives of professional footballers. Its findings offer insights that will prove helpful to officials, team managers and other relevant stakeholders involved in player care and athlete well-being. References Goffman, E. (1959). The presentation of the self in everyday life. Anchor Books. Hickey, C. (2016). Performing of the Pitch: An investigation of identity management strategies of professional footballers as part of their career transitions from the Premier League [Doctoral Thesis]. Durham University. Jacobs, F., Smits, F., & Knoppers, A. (2017). 'You don't realize what you see!' The institutional context of emotional abuse in elite youth sport. Sport in Society, 20(1), 126-143. https://doi.org/10.1080/17430437.2015.1124567 Kelly, S., & Waddington, I. (2006). Abuse, intimidation, and violence as aspects of managerial control in professional soccer in Britain and Ireland. International Review for the Sociology of Sport, 41(2), 147-164. https://doi.org/10.1177/1012690206075417 Markus, H., & Nurius, P. (1986). Possible selves. American Psychologist, 41(9), 954-969. https://doi.org/10.1037/0003-066X.41.9.954 Magrath, R. (2016). Inclusive masculinities in contemporary football: Men in the beautiful game. Routledge. McMahon, J., & McGannon, K. R. (2019). Acting out what is inside of us: Self-management strategies of an abused ex-athlete. Sport Management Review, 23(1), 23-38. https://doi.org/10.1016/j.smr.2019.03.008 Mountjoy, M., Brackenridge, C., Arrington, M., Blauwet, C., Carska-Sheppard, A., Fasting, K., Kirby, S., Leahy, T., Marks, S., Martin, K., & Starr, K. (2016). International Olympic committee consensus statement: Harassment and abuse (non-accidental violence) in sport. British Journal of Sports Medicine, 50(17), 1019-1029. https://doi.org/10.1136/bjsports-2016-096121 Plester, B. (2016). The complexity of workplace humour. Springer. Roderick, M. (2006). The work of professional football - A labour of love? Routledge.